Filogenetik 5 kultivar sagu dan spesies palmae lainnya berdasarkan penanda molekuler Mat-K - Wibawati, Zarima; Abbas, Barahima; Mustamu, Yohanis; Mawikere, Nouke Lenda; Noya, Alce Ilona (Cassowary, 2024)
ABSTRACT: Indonesia is one of the largest producers of sago in the world which is rich in genetic diversity. Improving superior sago varieties can be done through the plant breeding process to determine their genetic characteristics. Genetic diversity can be determined in several ways, namely morphological markers, molecular markers and cytological markers. Molecular markers can be done using several markers, namely nuclear markers (cell nucleus) and cytoplasmic markers. Chloroplast genome markers consist of rbcL and Mat-K. The gene most widely used in research on plant DNA barcoding throughout the world is the Mat-K gene. Analysis of sequencing results for this gene can use the MEGA program to produce kinship relationships. The method used in this experiment is a descriptive method. Based on the research results, it can be concluded that the resulting nucleotide sequence is 578 bp and has 192 amino acids. The genetic distance between the 5 sago cultivars and other palmae species ranged from 0.000-0.003. The phylogenetic tree shows that there are 2 groups with a boostrap value of 75, where in group 1 there is the species Metroxylon sago isolate Sago 15 which has a close relationship with Metroxylon warburgii when compared to other palmae species